2017
DOI: 10.20524/aog.2017.0191
|View full text |Cite
|
Sign up to set email alerts
|

Current and future biomarkers in colorectal cancer

Abstract: Colorectal cancer (CRC), one of the leading causes of death among cancer patients, is a heterogeneous disease and is characterized by diversions in multiple molecular pathways throughout its evolutionary process. To date, specific mutations in RAS and RAF genes are tested in everyday clinical practice along with mismatch repair gene deficiency, serving either as prognostic or predictive biomarkers, providing information for patient risk stratification and the choice of appropriate therapy. However, ongoing stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
93
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(94 citation statements)
references
References 86 publications
0
93
1
Order By: Relevance
“…A post‐hoc multivariate analysis of the VELOUR study profiled various subgroups with a greater survival benefit; patients with an ECOG performance status (PS) of 0 and any number of metastatic sites or with PS 1 and no more than one metastatic site presented an increase of 3.1 months in OS (16.2 vs 13.1 months). The prognostic role of RAS mutation status, tumour laterality, and the impact of first‐line treatment are acknowledged influences of outcome for treatment of mCRC with FOLFOX/FOLFIRI with or without cetuximab or bevacizumab, however little is known in the context of patients treated with FOLFIRI‐aflibercept. Analysis of outcome according to mutational status of KRAS , RAS and BRAF from the VELOUR translational study was recently published .…”
Section: Introductionmentioning
confidence: 99%
“…A post‐hoc multivariate analysis of the VELOUR study profiled various subgroups with a greater survival benefit; patients with an ECOG performance status (PS) of 0 and any number of metastatic sites or with PS 1 and no more than one metastatic site presented an increase of 3.1 months in OS (16.2 vs 13.1 months). The prognostic role of RAS mutation status, tumour laterality, and the impact of first‐line treatment are acknowledged influences of outcome for treatment of mCRC with FOLFOX/FOLFIRI with or without cetuximab or bevacizumab, however little is known in the context of patients treated with FOLFIRI‐aflibercept. Analysis of outcome according to mutational status of KRAS , RAS and BRAF from the VELOUR translational study was recently published .…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, mutations in APC and TP53 are enriched in left‐sided colorectal cancer. Recently, different patterns of mutations in those genes were identified as conferring differential prognoses in colorectal cancer …”
Section: Micrornas Cell Death and Oxaliplatin Resistancementioning
confidence: 99%
“…Recently, different patterns of mutations in those genes were identified as conferring differential prognoses in colorectal cancer. 49 Another mechanism for the development of resistance to chemotherapeutic drugs is by the activation of DNA repair mechanisms. It has been shown that the DNA repair pathways in cancer cells can reverse the DNA-damaging effect of oxaliplatin and promote resistance.…”
Section: Micrornas Cell Death and Oxaliplatin Resistancementioning
confidence: 99%
“…However, importantly, tumor cells originate from the same cell subtypes of one or more of the original healthy 200 cells in a tissue. Numerous methods exist for classifying (or diagnosing) a whole tissue biopsy as either cancerous or non-cancerous based on DNA genotyping [34], transcriptome profiling [35,36], or histochemistry [37,38]. Most of these methods work well, but are unable to accurately classify heterogeneity at a cellular level, and do not work if the percentage of tumor cells in a biopsy is small.…”
Section: Accurate Classification When Cells Types Are Imbalancedmentioning
confidence: 99%